2019
DOI: 10.3390/jsan8030040
|View full text |Cite
|
Sign up to set email alerts
|

Non-Intrusive Presence Detection and Position Tracking for Multiple People Using Low-Resolution Thermal Sensors

Abstract: This paper presents a framework to accurately and non-intrusively detect the number of people in an environment and track their positions. Different from most of the previous studies, our system setup uses only ambient thermal sensors with low-resolution, using no multimedia resources or wearable sensors. This preserves user privacy in the environment, and requires no active participation by the users, causing no discomfort. We first develop multiple methods to estimate the number of people in the environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Singh et al [31] compared the application of various Machine Learning (ML) classifiers for the detection and activity recognition of multiple human subjects using thermopile sensors. Similarly, Tateno et al [32] and Tao et al [33] used deep learning networks for fall detection and activity recognition respectively by utilizing ceiling-mounted sensors.…”
Section: A Localization Using Thermopile Sensorsmentioning
confidence: 99%
“…Singh et al [31] compared the application of various Machine Learning (ML) classifiers for the detection and activity recognition of multiple human subjects using thermopile sensors. Similarly, Tateno et al [32] and Tao et al [33] used deep learning networks for fall detection and activity recognition respectively by utilizing ceiling-mounted sensors.…”
Section: A Localization Using Thermopile Sensorsmentioning
confidence: 99%
“…Human activity can be recognized using various technologies namely sensors, video cameras, etc. [ 2 ], and using traditional or machine learning approaches [ 3 , 4 ]. Human activity recognition (HAR) is an important module for home monitoring systems for smart homes.…”
Section: Introductionmentioning
confidence: 99%
“…These types of systems can be used to provide safety to children and elderly people living in the home [5]. The combination of two emerging fields, Internet of Things (IoT) and Machine learning has achieved promising results for HAR [4,6]. The main data source for the task of activity recognition is sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al [ 18 ] showed that an adaptive thresholding method could help to detect people while using low-resolution heat sensors. Singh et al [ 19 ] used adaptive thresholding and the binary results for understanding whether people are on the floor, in a standing or sitting position. Next, they extended their work towards a multiple sensor application [ 20 ].…”
Section: Introductionmentioning
confidence: 99%